Successful Treatment of a Severe Vision-Threatening Paradoxical Tuberculous Reaction with Infliximab: First Pediatric Use. Issue 4 (April 2020) - Abo, Yara-Natalie; Curtis, Nigel; Butters, Coen; Rozen, Thomas H.; Marais, Ben J.; Gwee, Amanda
Abstract : A 7-year-old girl with tuberculous (TB) meningitis developed optochiasmatic arachnoiditis, a vision-threatening paradoxical reaction, after starting TB treatment including adjunctive steroid therapy. She was treated with infliximab with complete recovery. This is the first report of the use of a tissue necrosis factor α inhibitor for the treatment of a severe paradoxical TB reaction in a child.